The Total Impulse Study Of Solid Propellants Combustion Containing Activated Carbon From Coconut Shell As A Catalyst - Nur Rachman Supadmana Muda; I.N.G.Wardana I.N.G.Wardana; Nurkholis Hamidi; Lilis Yuliati; Aries Boedi Setiawan (International Conferences SDGs 2030 Challenges and Solutions, 2030)
This study investigates the capabilities of thrust, burn time, and total impulse from solid propellant materials. Attempts to increase the three variables are quite difficult because the thrust value is inversely proportional to the value of the burn time, it requires the catalyst as a regulator of the composition to produce an optimal variable value. The activated carbon from the coconut shell is used as a catalyst on a composite solid propellant material containing ammonium perchlorate (AP), hydroxyl terminated polybutadiene (HTPB) and aluminium (Al). The effect of adding coconut shell activated carbon may affect thrust parameters, burn time and total impulse rocket. The method of measuring parameters using rocket thrust test equipment. The mass of the test sample is 250 grams, the diameter of the test chamber is 20 mm, the length of the chamber is 200 mm. After going through the combustion process, it produces a graph and thrust value, total impulse and burning time. The thrust test results show that the test propellant 3 produces the best characteristic composition of 70% AP, 15% HTPB, 10% Al, and 5% activated carbon of 400 mesh with average thrust: 148.67N, total impulse: 637, 5 Ns, burn time: 4,288 s.